2015
DOI: 10.1021/acs.langmuir.5b02026
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating a Single Nucleotide Difference for Enhanced miRNA Detection Using Tunable Graphene and Oligonucleotide Nanodevices

Abstract: In this study we have reported our efforts to address some of the challenges in the detection of miRNAs using water-soluble graphene oxide and DNA nanoassemblies. Purposefully inserting mismatches at specific positions in our DNA (probe) strands shows increasing specificity against our target miRNA, miR-10b, over miR-10a which varies by only a single nucleotide. This increased specificity came at a loss of signal intensity within the system, but we demonstrated that this could be addressed with the use of DNas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…Some reports have illustrated that, by intentionally introducing a base mutation into the DNA probe strand, the discrimination capability against the target oligonucleotide over other highly homologous family sequences can be improved . Inspired by this finding, we postulated that, by introducing a base mutation into the let‐7a recognition region of the fully complementary padlock probe C, the discrimination power of the assay towards base mismatch would be enhanced.…”
Section: Resultsmentioning
confidence: 91%
“…Some reports have illustrated that, by intentionally introducing a base mutation into the DNA probe strand, the discrimination capability against the target oligonucleotide over other highly homologous family sequences can be improved . Inspired by this finding, we postulated that, by introducing a base mutation into the let‐7a recognition region of the fully complementary padlock probe C, the discrimination power of the assay towards base mismatch would be enhanced.…”
Section: Resultsmentioning
confidence: 91%
“…A new GO-polymer-oligonucleotide (nGO-PEGMA/M2) and enzyme ( DNase I ) system able to detect miR-10b in an RNA pool taken from metastatic breast cancer cells were reported by Robertson et al [ 90 ]. The insertion of a specific mismatch fragment into the probe sequence induced an increase of specificity towards miR-10b, an oligonucleotide overexpressed in breast cancer.…”
Section: Circulant Tumor Nucleic Acids (Ctnas)mentioning
confidence: 99%
“…Robertson et al found that the addition of DNase I to a nanodevice mixture could improve sensitivity, but because of enzyme activity on the surface of adsorption probes, unwanted background signals were generated . The attachment of (poly(ethylene glycol) methyl ether methacrylate) PEGMA polymers eliminated the undesired enzymatic activity and steady increase in background fluorescence by blocking the access of DNase I to the nanodevice surface.…”
Section: State‐of‐the‐art Protocols For High‐quality Mirna Detectionmentioning
confidence: 99%